Violação dos direitos humanos no Tocantins causada pelos crimes dolosos contra a vida e a invisibilidade da sua tipificação por classe social, por questão étnico-racial e gênero - Bellezzia, Cibele Maria (Universidade Federal do Tocantins, 2016)
This report has as its goal to register the activities develloped throughout the Master Program of Jurisdictional Providing and Human Rights of Tocantins Federal University, together with Tocantins School of Magistrates (ESMAT), in order to verify the impact of the violation of human rights in Tocantins caused by intentional crimes against life in the branch of the invisibility of its criminalization by social class and ethinic, ratial and gender matters.